Sequence-specific DNA modification in Neisseria gonorrhoeae. - Korch, C (1983)
Neisseria gonorrhoeae 82409/55(pJD1) is postulated to possess six DNA sequence-specific cytosine methyltransferases and one DNA sequence-specific N6-adenine methyltransferase. From the DNA sequencing of the plasmid pJD1 (manuscript in preparation) by a modification of the Maxam and Gilbert chemical cleavage procedure, the cytosine methylation specificities were demonstrated. Five of these methylating enzymes and their respective specificities are M . NgoI (formula; see text) does not methylate the cytosine of its recognition sequence, in agreement with a detected adenine modification. A biological implication of these different DNA methylating activities is discussed.